Determinan Risiko Sistematis pada Perusahaan Rokok di Indonesia - Tri Utomo Prasetyo (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2020)
This study aims to examine the effect of company size, sales growth, and financial leverage on systematic risk in the Indonesian cigarette industry. The variable total assets is used to proxy for company size, long term debt-to-equity ratio for financial leverage, and beta stock—collected from the third party—for systematic risk. Four cigarette companies listed on the Indonesia Stock Exchange are sampled for this study in the 2016Q2-2018Q4 period. Hypothesis testing is done using panel data regression. The results show that ceteris paribus, company size and financial leverage have a positive effect on systematic risk, while sales growth statistically has no effect.